The Analysis of Psychological Factors on Students' Interest Towards the Independent Campus Internship Program Using Structural Equation Modeling Partial Least Square - Hiariey, Arlene Henny; Ode, Yayan (Jurnal Matematika, Statistika dan Komputasi, 2023)
Internship is part of a job training system that is held in an integrated manner between training at training institutions by working directly under the guidance and supervision of instructors or more experienced workers/laborers, in the process of producing goods and / or services in the company, in order to master certain skills or expertise. The internship program is part of the Merdeka Belajar Kampus Merdeka (MBKM) program, which provides opportunities for students from various universities in Indonesia in coordination with the ministry of education, culture, research, and technology (Kemendikbudristek) to learn in the world of work. The object in this study was focus on a student of the Statistics Study Program at Pattimura University. The purpose of this study is to model SEM-PLS based on cases from the results of questionnaire analysis, determine indicator variables that are feasible to be used as an influence on latent variables based on the SEM-PLS method, and identify the influence of exogenous latent variables, namely Motivation, Value Perception of Internship Program. SEM is one of the Multivariate data analysis methods which is a statistical analysis method to analyze several variables simultaneously. Based on the results and discussion in this study is modeling the influence of motivation, Perception of Internship Program Value, Perception of Self-Ability, and Perception of Specific Support for Student Interest resulting in the following structural equations:. These results are valid, reliable, and have been evaluated both through reflective and formative measurement processes.